Analisis Semiotika Representasi Budaya Adat Jawa dalam Serial Drama “Gadis Kretek” - Ralfi Firmansyah; Didi Permadi; Inas Sany Muyassaroh (SENTRI: Jurnal Riset Ilmiah, 2026)
Drama series as part of popular literary works not only function as a medium of entertainment, but also play an important role in representing the social and cultural realities of society. With the development of digital technology, drama series are now increasingly easily accessible through various streaming platforms, one of which is Netflix. Gadis Kretek, a series adapted from a novel by Ratih Kumala directed by Kamila Andini and Ifa Isfansyah, is a representative example in presenting Javanese traditional culture in a strong and complex way, especially in the socio-historical context of Indonesia in the 1960s. This study aims to analyze the representation of Javanese traditional culture in the Gadis Kretek series using Roland Barthes's semiotic approach. The research method used is descriptive qualitative with Barthes's two-stage semiotic analysis technique, which includes denotative, connotative, and mythical meanings. Primary data was obtained from several selected scenes in the Gadis Kretek series that contain Javanese cultural symbols, while secondary data was obtained through library research from scientific journals and supporting literature. The analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that Javanese cultural symbols such as kebaya, Sido Asih batik cloth, jasmine garlands, blangkon, and chignon are not only displayed as visual elements, but also contain ideological meanings that represent the values ​​of harmony, social hierarchy, spirituality, and the construction of gender roles in Javanese culture. Through semiotic reading, these symbols form a cultural myth that subtly reproduces traditional values ​​and patriarchal structures. Thus, Gadis Kretek not only presents visual entertainment, but also becomes a discursive space that reflects and constructs Javanese cultural identity in popular media.